Preoperative lateral subluxation of the patella is a predictor of poor early outcome of Oxford phase-III medial unicompartmental knee arthroplasty - Munk, Stig (Informa Healthcare, 2011)
BACKGROUND AND PURPOSE: There is disagreement in the literature about the importance of patellofemoral joint degeneration and knee pain for the outcome of unicompartmental knee arthroplasty (UKA). We therefore investigated the importance of selected predictors including patellofemoral joint degeneration and the location of preoperative knee pain for the early outcome of UKA. PATIENTS AND METHODS: The study group comprised 260 consecutive patients from 5 hospitals who underwent Oxford UKA for anteromedial osteoarthritis. Data were collected at baseline and included pain location, radiologically observed degeneration of the patellofemoral joint including subluxation of the patella, intraoperative cartilage status of the patellofemoral joint, disease-specific knee status, and Oxford knee score (OKS). Outcomes were evaluated after 1 year using the OKS, global patient satisfaction, and global patient result. RESULTS: The average OKS score at baseline was 24 (SD 7), and it was 40 (SD 8) at the 1-year follow-up. 94% of the patients claimed improvement after the operation and 90% were satisfied with the UKA. Lateral subluxation of the patella was a predictor of poor outcome, and the preoperative OKS score was also a predictor of outcome. Full-thickness cartilage loss at any location gave a similar outcome to that with a normal or near-normal joint surface, and likewise, preoperative anterior knee pain was not a predictor of outcome. INTERPRETATION: We conclude that the good early outcome after UKA in this study is in line with the best reported results. Patellofemoral degeneration should not be considered a contraindication to Oxford UKA. Patients with lateral subluxation of the patella have an increased risk of a poor result after UKA and should preferably be offered a total knee replacement.